Origins and destinations: the making of the second generation - Luthra, Renee (Russell Sage Foundation, 2018)
Origins and destinations -- Bringing the international back in: a new perspective -- The international perspective -- The importance of context -- Getting ahead: institutions, ethnicity, and international nfluences -- Acquiring citizenship -- Exercising citizenship -- Cross-border connections -- Ethnicity: crossing blurry boundaries -- Conclusion: the making of the second generation